How NFIB v. Sebelius Affects the Constitutional Gestalt - Lawrence B. Solum (Washington University Law Review, 2013)
This Essay examines the effects of the Supreme Court‘s decision in National Federation of Independent Business v. Sebelius, in which the Court addressed the constitutionality of the Affordable Care Act. More precisely, what effects will NFIB have on the law—especially constitutional law? We can divide these effects into two general categories, direct and indirect. "Direct legal effects" are those created by and through legal norms. They include the operation of legal orders (the mandate in an appellate opinion) and legal rules (stare decisis and the doctrine of law of the case). "Indirect legal effects" are mediated by causal processes that are not themselves instantiations of legal rules. For example, if a legal decision affects politics, and then the political change affects the law, that change would constitute an indirect legal effect.
Keywords: Affordable Care Act; ACA; NFIB; constitution; Sebelius; Supreme Court